The murine enterocyte cell line Mode-K is a novel and reliable in vitro model for studies on gluten toxicity. (June 2020) - Luongo, Diomira; Treppiccione, Lucia; Maurano, Francesco; Rossi, Mauro; Bergamo, Paolo
Abstract: The resemblance of physiological traits of cell lines with their target/original tissue is an important prerequisite for the choice of the in vitro model. Although cytoprotective defenses, activated by the nuclear factor erythroid 2-related factor2 (Nrf2), have a preeminent importance in intestinal protection, nevertheless their levels in in vitro models have been never compared with those of their original tissue. Basal level of Nrf2-mediated defenses in murine enterocyte cells (Mode-K) and in human colon adenocarcinoma cells -at differentiated (DCaco2) or confluent stage (CCaco2)- were compared with those found in mouse or human duodenum. The pro-oxidant and cytotoxic effects of peptic-tryptic digest of gluten prepared from wheat bread (PT-b ), einkorn (PT-e ) or durum wheat (PT-d ) were evaluated in Mode-k and DCaco2 by combining enzymatic, immune-enzymatic and real-time PCR assay. The results presented reveal that Mode-k cells resemble cytoprotective defenses of human/murine duodenum and are more susceptible to pro-oxidant, cytotoxic and pro-inflammatory effect of gliadin digest (in comparison with Caco2). Prolamins digests from the considered wheat exhibit different inhibitory effect on Nrf2-mediated defenses (PT-b  > PT-e  > PT-d ). These data indicate, for the first time, that Mode-k are a reliable model for investigating wheat prolamins toxicity and for evaluating the signaling pathway of gluten-associated disease. Graphical abstract: The resemblance of cytoprotective defenses of Mode-K cells with human and murine duodenum along with their higher susceptibility to the toxic effect triggered by prolamin from bread wheat (PT-b) indicated their higher suitability for evaluating prolamin toxicity (in comparison with Caco-2 cells).Next, Mode-K were used to evaluate the different toxicity (pro-oxidant/pro-inflammatory effects) triggered by prolamin from PT-b or from durum wheat (PT-d). Notably, significantly higher TNF-a, IL-6, CXCL-2 and COX-2 in PT-stimulated Mode-K cells indicates their ability to replicate typical symptoms of gliadin-induced inflammation (celiac disease). Image 1 Highlights: Antioxidant/detoxifying (cytoprotective) defences of murine enterocyte cells (Mode-K) resembles those of mouse duodenum. Mode-K mimics cytoprotective defences of human duodenum better than differentiated Caco2 (DCaco2). Mode-K cells are more responsive than DCaco2 to cytotoxic/pro-inflammatory effects of gliadin from bread wheat (PT-b). Mode-K are more susceptible to pro-oxidant/pro-inflammatory effects triggered by PT-b than to T. durum wheat (PT-d).